Hemocompatible polyethersulfone/polyurethane composite membrane for high‐performance antifouling and antithrombotic dialyzer. Issue 1 (25th April 2014) - Yin, Zehua; Cheng, Chong; Qin, Hui; Nie, Chuanxiong; He, Chao; Zhao, Changsheng
Abstract Researches on blood purification membranes are fuelled by diverse clinical needs, such as hemodialysis, hemodiafiltration, hemofiltration, plasmapheresis, and plasma collection. To approach high‐performance dialyzer, the integrated antifouling and antithrombotic properties are highly necessary for the design/modification of advanced artificial membranes. In this study, we propose and demonstrate that the physical blend of triblock polyurethane (PU) and polyethersulfone (PES) may advance the performance of hemodialysis membranes with greatly enhanced blood compatibility. It was found that the triblock PU could be blended with PES at high ratio owing to their excellent miscibility. The surfaces of the PES/PU composite membranes were characterized using attenuated total reflectance‐Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, water contact angle measurement, and surface ζ‐potentials. The results indicated that the membrane surfaces were assembled with hydrophilic segregation layer owing to the migration of amphiphilic PU segments during membrane preparation, which might confer the composite membranes with superior hemocompatibility. The cross‐section scanning electron microscopy images of the composite membranes exhibited structure transformation from finger‐like structure to sponge‐like structure, which indicated that the composite membrane had tunable porosity and permeability. The further ultrafiltration experiments indicated that the composite membranes showed increased permeability and excellent antifouling ability. The blood compatibility observation indicated that PES/PU composite membranes owned decreased protein adsorption, suppressed platelet adhesion, and prolonged plasma recalcification time. These results indicated that the PES/PU composite membranes exhibited enhanced antifouling and antithrombotic properties than the pristine PES membrane. The strategy may forward the fabrication of blood compatible composite membranes for clinical blood dialysis by using the various functional miscible polymers. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 97–105, 2015.